COVID‐19 pandemic and health care disparities in head and neck cancer: Scanning the horizon. Issue 7 (20th June 2020) - Graboyes, Evan; Cramer, John; Balakrishnan, Karthik; Cognetti, David M.; López‐Cevallos, Daniel; de Almeida, John R.; Megwalu, Uchechukwu C.; Moore, Charles E.; Nathan, Cherie‐Ann; Spector, Matthew E.; Lewis, Carol M.; Brenner, Michael J.
Abstract: The COVID‐19 pandemic has profoundly disrupted head and neck cancer (HNC) care delivery in ways that will likely persist long term. As we scan the horizon, this crisis has the potential to amplify preexisting racial/ethnic disparities for patients with HNC. Potential drivers of disparate HNC survival resulting from the pandemic include (a) differential access to telemedicine, timely diagnosis, and treatment; (b) implicit bias in initiatives to triage, prioritize, and schedule HNC‐directed therapy; and (c) the marked changes in employment, health insurance, and dependent care. We present four strategies to mitigate these disparities: (a) collect detailed data on access to care by race/ethnicity, income, education, and community; (b) raise awareness of HNC disparities; (c) engage stakeholders in developing culturally appropriate solutions; and (d) ensure that surgical prioritization protocols minimize risk of racial/ethnic bias. Collectively, these measures address social determinants of health and the moral imperative to provide equitable, high‐quality HNC care.